Quantifizierung des Einflusses der äußeren Produktgestaltung auf die Geschmacksbewertung und auf die Kaufbereitschaft bei Wein mittels eines Charakteristikamodells; Quantifying the Influence of Product Design on Perceived Taste and Purchase Intent for Wine Using a Characteristics Model - Gergely Szolnoki Szolnoki; Dieter Hoffmann; Roland Herrmann (German Journal of Agricultural Economics (GJAE), 2011)
– A substantial expansion of wine supply has induced a strong product proliferation on the market. It is not only the taste of wines that has become more diversified, but quality signals are increasingly utilized, too. Quality signals include information on the wine bottle, such as origin, grape variety or brands. Additionally, there is a strong trend towards using the product design, i.e. bottle type or style of the wine label, as an instrument of product differentiation. The objective of this article is to analyze whether the product design affects the perceived taste of wine and the willingness to buy a wine. Primary data, which have been collected from an experiment combined with a survey of wine consumers, reveal that product design strongly affects the willingness to buy a wine. This strong effect occurs when the wine is tasted prior to the purchase decision. Interestingly, the product design affects consumers' taste evaluation of the wine that is crucial for the consequential effects on the willingness to buy. An alternative modeling approach with a direct impact of product design on willingness to buy strongly underestimates the role of product design. A cluster analysis additionally reveals that product design and other quality signals do matter in some wine consumer segments but less in others.
Keywords: 330; Wein; Produktinformation; Produktqualität; Konsumentenverhalten; Deutschland